Co-expression of PD1+ and HLA-DR+ in CD8+ T cells is increased in tonsils of children with EBV primary and persistent infection - Amarillo, María Eugenia; Lindl, Karen; Lapido, Veronica; Rojas Campión, Ignacio E.; Collado, M. Soledad; Speratti, Johanna; Valerio, Andrea; Baz, Plácida; De Matteo, Elena; Billordo, L. Ariel; Chabay, Paola (Frontiers in Immunology, 2025)
IntroductionEpstein–Barr virus (EBV) infects B lymphocytes and establishes lifelong persistence in the B cells. While systemic T-cell responses have been well characterized, the local immune response at the site of viral entry in children from undeveloped countries remains poorly understood.MethodsTonsillar CD4 and CD8 T cells in 32 pediatric patients undergoing tonsillectomy were classified as primary infected (PI), EBV carriers (EC), and non-infected children by serology. T-cell subsets were assessed by flow cytometry, whereas LMP1 and EBNA2 viral proteins were evaluated by immunohistochemistry.ResultsA higher percentage of activated HLA-DR+ CD8 T cells in PI patients was demonstrated. Notably, PD-1 expression was increased in both PI and EC, in particular in activated HLA-DR+ CD8 T cells. Positive correlations of EBNA2 with follicular helper T cells and Th1 cells, as well as a negative correlation between EBNA2 and activated CD8 T cells, were observed.DiscussionThese findings suggest that, during asymptomatic primary infection by EBV, activated CD8 T cells are observed, but they may be cells that may exhibit features of exhaustion, which probably explains the absence of symptoms. PD-1 expression in CD8 T cells remains in EC. Additionally, Tfh, Th1, and CD8 T cells may influence the expression of EBNA2 and LMP1 latent viral antigens in tonsils.